40Ar-39Ar step heating ages of North American tektites and of impact melt rock samples from the Chesapeake Bay impact structure. (15th June 2019) - Assis Fernandes, V.; Hopp, J.; Schwarz, W.H.; Fritz, J.P.; Trieloff, M.; Povenmire, H.
Abstract: This study presents 40 Ar- 39 Ar step heating ages of four North American tektites (three bediasites and one georgiaite) and of two groundmass samples extracted at different depths from clast-rich impact melt rocks (CB-W61 and CB-W84) recovered by the USGS-ICDP Eyreville B drill-core about 9 km from the centre of the Chesapeake Bay impact structure. Radiometric age determination on both North American tektites and impact melt rocks from within Chesapeake Bay crater offers the first possibility to confirm the origin of these tektites. For this aim, argon isotopic data from 13 samples/aliquots of tektite rims, cores and bulk, and 4 samples/aliquots from two impact melt rocks were obtained over 15 to 26 step heating extractions. Age spectra of all tektite samples show plateaux comprising 62–98% of the 39 Ar release over consecutive intermediate and high temperature heating steps. Few low temperature extractions indicate excess 40 Ar. Inverse isochron 40 Ar/ 36 Ar intercepts of tektite samples are indistinguishable from air (295.5). However, impact melt rock spectra presented complex Ar-release affecting primarily the low temperature heating-steps. Inverse isochrones indicate excess argon from which the 40 Ar/ 36 Ar intercept was used to correct the age calculation. CB-W61 and CB-W61-2 40 Ar/ 36 Ar intercepts are 354.5 ± 2.5 and 327.2 ± 6.3, respectively, and those for CB-W84 and CB-W84-2 are 332.0 ± 7.3 and 329.6 ± 5.6, respectively. The inverse isochron weighted mean age (according to currently suggested K-decay constants revisions by Schwarz et al. (2011) and Renne et al. (2011)) for all four tektites is 34.86 ± 0.25 Ma (MSWD = 0.96, P = 0.41; n = 4) and for the two impact melt rocks is 37.16 ± 3.65 Ma (MSWD = 0.83, P = 0.36). The combined tektite and impact melt rocks isochron mean age of 34.86 ± 0.23 (0.32) Ma (MSWD = 0.87, P = 0.43) is slightly – though not significantly – higher than the plateau mean age of 34.55 ± 0.27 (0.36) Ma (MSWD = 0.66, P = 0.62). Placing this age in the Global Stratotype Section and Point (GSSP) marine section exposed at Massignano, Italy, it falls below the Eocene/Oligocene (E/O) boundary overlapping with the 10.28 m Ir-anomaly. These results agree within errors with previously reported ages of 35.20 ± 0.54 Ma, especially those derived from K-Ar and Ar-Ar total fusion analysis. An age of 34.86 ± 0.32 Ma sets the Chesapeake Bay impact event close to the youngest of the three Ir anomalies at ∼35.0 Ma in the case the impactor was Ir-rich (e.g, a chondrite, primitive achondrite, stony-iron or iron meteorite). The concordance with the E/O boundary at ∼33.9 Ma seems only marginally possible, and only if the Ir contribution from the ejecta were, potentially, due either to its small amount becoming diluted in the geologic record or the impactor being Ir poor, e.g., of differentiated achondritic composition. This study also brings to front the need to re-establish the stratigraphic and palaeo-magnetic correlations across the globe for the Ir-anomalies and the magneto-stratigraphy during the mid- to late-Eocene and early-Oligocene, and the need to re-evaluate the markers for the Eocene-Oligocene boundary.